Penggunaan Media Sosial Terhadap Pemahaman Nilai-Nilai Islam pada Generasi Muda - Adelia Ermalyona; Aria Hermawan (AJER: Advanced Journal of Education and Religion, 2025)
The use of social media among young generations has become a global phenomenon that influences various aspects of life, including the understanding of Islamic values. Social media provides easy access to religious information through various content, such as online lectures, short videos, and Islamic infographics, which can enhance young people's comprehension of Islamic teachings. However, social media also presents challenges, such as the spread of invalid information, exposure to radical ideologies, and content that contradicts Islamic values. This article aims to analyze the positive and negative impacts of social media on the understanding of Islamic values among young people and to identify strategies for optimizing social media as a tool for spreading Islamic teachings. The findings highlight that digital literacy, the involvement of religious figures, and the development of creative Islamic content are crucial steps to maximize the benefits of social media while minimizing its harmful effects. With the right approach, social media can become an effective tool in fostering a generation that comprehends and practices Islamic values comprehensively.